Applications of knowledge management in the area of librarianship and information scence: a systematic review (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
The knowledge management (KM) has become an important guideline for the Information and Knowledge Society, as well as for libraries. Thus, this article presents a literature review using a systematic approach, with the proposition of identifying trends and applications of knowledge management in the areas of Information Science and/or Library Science. It has been noticed that there are differences between the concepts of information management and knowledge management characterized as barriers to the implementation of KM. Libraries have often developed KM activities (especially regarding the sharing of knowledge, through Web 2.0 features). The uses currently applied are related to the use of blogs, wiki tools, shared classification systems (tagging), social networks, among others. But in some cases, the libraries are not properly aware of their work. It is necessary that they make KM a part of their routines and think of it in a systematic way, in order to channel resources, planning, among other things, and benefit from the improvements that can be achieved through KM, perfecting their services and satisfying their users. Keywords: Knowledge Management. Information Management. Librarianship. Information Science. Library Science. Knowledge Management Practices. Link para o texto completo (PDF)http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/2987/2394